Targeting the Malaria Parasite cGMP-Dependent Protein Kinase to Develop New Drugs - Baker, David A.; Matralis, Alexios N.; Osborne, Simon A.; Large, Jonathan M.; Penzo, Maria (Frontiers in Microbiology, 2020)
The single-celled apicomplexan parasite Plasmodium falciparum is responsible for the majority of deaths due to malaria each year. The selection of drug resistance has been a recurring theme over the decades with each new drug that is developed. It is therefore crucial that future generations of drugs are explored to tackle this major public health problem. Cyclic GMP (cGMP) signaling is one of the biochemical pathways that is being explored as a potential target for new antimalarial drugs. It has been shown that this pathway is essential for all of the key developmental stages of the complex malaria parasite life cycle. This gives hope that targeting cGMP signaling might give rise to drugs that treat disease, block its transmission and even prevent the establishment of infection. Here we review previous work that has been carried out to develop and optimize inhibitors of the cGMP-dependent protein kinase (PKG) which is a critical regulator of the malaria parasite life cycle.